Gentry variety of the Belarusian language in early works of Janka Kupala: to the problem statement - Zaprudski, Siarhiej M. (Journal of the Belarusian State University. Philology, 2022)
The article attempts to identify the gentry variety of the written Belarusian standard language, as based on scientific literature, Janka Kupala’s collection «The little flute» (1908) and his play «Paulinka» (1912). In the first third of the 20th century in Belarus there was a large number of the gentry who cultivated the Belarusian gentry speech, the Belarusian peasant speech, the Polish language in its regional form and various intermediate varieties, as well as the Russian language depending on communication situation and other circumstances. When interpreting the linguistic material of the Belarusian standard language of the first third of the 20th century the following set of reference points is used: the folk (peasant) speech, Belarusian literary language of the 19th – early 20th centuries, old Belarusian written language, Russian, Polish and Ukrainian standard languages. The lack of such a reference point as the gentry variety (cultural koine) has negative consequences since an important channel of entry of many Polonisms and diverse cultural lexis into the Belarusian standard language is not taken into account. The Polish language was more important in the early stage of Janka Kupala’s work than is commonly believed; Polish influences are recorded not only in vocabulary, but also in grammar. The gentry variant of the written Belarusian language was used as a certain register, which gave a peculiar elite flavour to the language of certain fragments of artistic works or those entire works, or was sometimes perceived as a representative of the Belarusian standard language in general.